Analysis of the miRNA expression from the adipose tissue surrounding the adrenal neoplasia - Concistrè, Antonio; Petramala, Luigi; Circosta, Francesco; Romagnoli, Priscilla; Soldini, Maurizio; Bucci, Marco; De Cesare, Domenico; Cavallaro, Giuseppe; De Toma, Giorgio; Cipollone, Francesco; Letizia, Claudio (Frontiers in Cardiovascular Medicine, 2022)
Background Primary aldosteronism (PA), is characterized by several metabolic changes as insulin resistance, metabolic syndrome, and adipose tissue (AT) inflammation. Mi(cro)RNAs (miRNAs) are a class of noncoding small RNA molecules representing critical regulators in several cellular process associated with adipose tissue dysfunction. Aim of this study was to evaluate the expression of some miRNAs in visceral and subcutaneous AT in patients undergoing adrenalectomy for aldosterone-secreting adrenal adenoma (APA), respect samples of AT obtained in patients undergoing adrenalectomy for non-functioning adrenal mass (NFA). Methods: Quantitative expression of selected miRNA using PCR real time was analyzed in surrounding adrenal neoplasia, peri-renal and subcutaneous AT samples of 16 adrenalectomized patients (11 patients with APA and 5 patients with NFA). Results Real-time PCR cycles for miRNA 132, miRNA 143 and miRNA 221 in fat surrounding adrenal neoplasia and in peri-adrenal AT were significantly higher in APA than in NFA patients. Unlike NFA patients, miRNA 132, miRNA 143, miRNA 221 and miRNA 26b were less expressed in surrounding adrenal neoplasia AT compared to subcutaneous AT in APA patients. Conclusion This study, conducted on tissue expression of miRNAs, highlights the possible pathophysiological role of some miRNAs in determining the metabolic alterations in PA patients.